Illicit drugs seizures in 2013–2018 and characteristics of the illicit market within the Neapolitan area. (April 2021) - Silvestre, A.; Basilicata, P.; Coraggio, L.; Guadagni, R.; Simonelli, A.; Pieri, M.
Highlights: Toxicological data on seized material in the Naples area in 2013–2018 are presented. Unlike European trends there is a prevalence of herbal on resin derivatives. Deferred people were male, 30–40 yr, or younger for cannabis. Areas with higher amounts of seizures are at the higher risks of mafia homicides. Mafia proceeds from classical drugs may account for the absence of NPS. Abstract: The study presents results of toxicological analysis performed on seized material in Neapolitan area in the period from 2013 to 2018. A constancy in THC and heroin percentages is evidenced (%THC ~10% and ~11.5% for marijuana and hashish; heroine: 20–24%), with mean values exceeding the European data. Data on cocaine revealed a constant increment of active principle percentage over the studied period (from 40% in 2013 to ~65% in 2018), with peak of 70% in 2017; also, number of samples exceeding the mean value increased over years. Active principles contents resulted higher than the ones reported in other Italian area ever the same period; marijuana was prevalent on hashish, confirming an Italian trend different from other European countries. A map of the Campania region evidenced two main "storage" districts, one corresponding to the city center and the second located in the northern part. If compared with literature data on the presence of local mafia, these areas are perfectly superimposable to those with the highest risk of homicides, thus confirming the degree of radicalization of local organizations and the relative weight of proceeds from drugs sale. Moreover, such radicalization within the territory seems to be the main reason of the absence of new psychoactive substances among the seized material.